(untitled) (Texas Journal of Medical Science, 2025)
This article explores key strategies and interventions for the prevention of gynecological diseases, which pose significant health challenges for women worldwide. Effective preventative measures discussed include regular screenings, vaccination against HPV, lifestyle modifications, hormonal balance maintenance, and awareness of individual risk factors. Early detection and proactive management play a crucial role in mitigating the incidence and severity of gynecological conditions such as uterine fibroids, endometriosis, cervical cancer, and others. The implementation of comprehensive prevention programs is essential for promoting women’s reproductive health and overall well-being. This article aims to provide an evidence-based overview of actionable steps for both healthcare providers and women to reduce the burden of gynecological diseases.